2020
DOI: 10.1183/23120541.00265-2019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-acting β-agonists/glucocorticoids on human airway epithelial cell cytokine, transcriptomic and oxidative stress responses to cannabis smoke

Abstract: Cannabis is one of the most widely consumed drugs in the world, with an estimated 180 million annual users globally [1]. Recent trends of legalisation of medicinal and/or recreational cannabis have led to increased access to cannabis products that will likely lead to increased use over the coming years. Inhalation of combusted cannabis is by far the most prevalent form of cannabis use, reported by 89% of users in the 2018 Canadian Cannabis Survey [2]. Chemically, cannabis smoke includes pharmacologically activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Airway epithelial cells carry out a number of functions such as providing a physical barrier against microbial infiltration, maintaining the inflammatory microenvironment, and releasing immune mediators to recruit leukocytes to the site of insult. It has been demonstrated that the inhalation of air pollution, tobacco smoke, and cannabis smoke can compromise airway epithelial function [30][31][32]. Notably, recent findings show that cannabis smoke exposure can lead to impaired airway epithelium barrier integrity, attenuated antiviral capacity, and exacerbated inflammatory response to immune challenges [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Airway epithelial cells carry out a number of functions such as providing a physical barrier against microbial infiltration, maintaining the inflammatory microenvironment, and releasing immune mediators to recruit leukocytes to the site of insult. It has been demonstrated that the inhalation of air pollution, tobacco smoke, and cannabis smoke can compromise airway epithelial function [30][31][32]. Notably, recent findings show that cannabis smoke exposure can lead to impaired airway epithelium barrier integrity, attenuated antiviral capacity, and exacerbated inflammatory response to immune challenges [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the inhalation of air pollution, tobacco smoke, and cannabis smoke can compromise airway epithelial function [30][31][32]. Notably, recent findings show that cannabis smoke exposure can lead to impaired airway epithelium barrier integrity, attenuated antiviral capacity, and exacerbated inflammatory response to immune challenges [31,32]. However, the contribution of the endocannabinoid system to these observations has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled cannabis smoke travels through the upper and lower airways, with airway epithelial cells being a major site of first contact. We have demonstrated with an in vitro model of airway epithelial cell culture that cannabis smoke induces a concentration-dependent reduction in airway epithelial cell viability, barrier function, while promoting pro-inflammatory cytokine secretion (31, 32). Complementary profiling of human epithelial cells isolated via bronchial brushings has demonstrated cannabis consumption-dependent elevations in TLR5, TLR6, and TLR9 gene expression(101).…”
Section: Discussionmentioning
confidence: 99%
“…Airway epithelial cells carry out a number of functions such as providing a physical barrier against microbial infiltration, maintaining the inflammatory microenvironment, and releasing immune mediators to recruit leukocytes to the site of insult. It has been demonstrated that the inhalation of air pollution, tobacco smoke, and cannabis smoke can compromise airway epithelial function(30-32). Notably, recent findings show that cannabis smoke exposure can lead to impaired airway epithelium barrier integrity, attenuated antiviral capacity, and exacerbated inflammatory response to immune challenges(31, 32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation